V postelji s sovražnico - Sunčič, Maja (Monitor ISH, 2004)
In bed with the enemy. The article analyses the implicit link between the woman in antiquity and her marital bed, questioning the very existence of a "happy marriage" in the Greek imaginary. The traumatised tragic heroine cannot hope for happiness or even love in bed and marriage: indeed, even the so-called "ideal" marriage of Alcestis and Admetus is represented by the negative, the absence of one spouse. The bed presents a means of escape for the heroines, a symbolic dissolution of an unhappy marriage: Medea torches her bed, while Alcestis, Deianeira and others abandon theirs by choosing a tragic death. While Penelope languishes in an empty bed, tragic heroines may thus not be tragic at all in their decision to die and never sleep in theirs again.
Keywords: antika; classical antiquity; marriage; zakonska zveza; woman; ženske; družbeni položaj; zakonski odnosi; mitologija; mythology